Ecological Quality Analysis of the Rezekne River after Zooplankton (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
During seasonal studies 2012 (August/October), samples of zooplankton were collected and analyzed according standard method. Chemical quality of the Rezekne River's water investigated. Changes of quantitative and qualitative characteristics, saprobity index, species diversity (Shannon- Wiener index) and Renkonen index were employed for the analysis of zooplankton community structure in the Rezekne River. The Rezekne River saprobity varies from o – saprobity to β – mesosaprobity. The lowest ecological quality was determined in the leg of the Rezekne River in the territory of Rezekne city, which characterises with decrease in the total zooplankton abundance and species diversity according to Shannon - Wiener index, increase of saprobity.